2014
DOI: 10.12793/tcp.2014.22.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Development of a LC-MS/MS for Quantification of Venlafaxine in Human Plasma and Application to Bioequivalence Study in healthy Korean Subjects

Abstract: A simple, rapid and selective liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) is developed and validated for quantification of venlafaxine in human plasma with simple liquid-liquid extraction step consisted of extraction with ether and dichloromethane for 10 min and mixing with 1 M sodium acetate in human plasma using fluoxetine as an internal standard (IS). The analyte are separated using an isocratic mobile phase consisted of acetonitrile and 5 mM ammonium formate (4/3, v/v) on a isocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Kang et al () developed a high‐throughput HPLC–MS/MS method for venlafaxine quantitation with fluoxetine as the IS. Human plasma samples were liquid–liquid extracted by ether–dichloromethane 7:3, which was unique because ethyl acetate was the dominant choice of extractant in almost all other recent LLE processes.…”
Section: Techniquesmentioning
confidence: 99%
“…Kang et al () developed a high‐throughput HPLC–MS/MS method for venlafaxine quantitation with fluoxetine as the IS. Human plasma samples were liquid–liquid extracted by ether–dichloromethane 7:3, which was unique because ethyl acetate was the dominant choice of extractant in almost all other recent LLE processes.…”
Section: Techniquesmentioning
confidence: 99%
“…Aer a careful literature survey, it was revealed that most of the analytical methods for determination of VEN are HPLC methods. [4][5][6][7][8][9][10][11][12] However, these methods face some drawbacks including the cost of equipment, consumption of large volumes of solvents and requirement of several pretreatment procedures for biological samples. Also, thin layer chromatography (TLC) was described for VEN analysis in bulk and capsules.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic estimation of Venlafaxine HCl was reported by using few HPLC methods either in combination or individual in pharmaceutical dosage form [9][10][11][12]. In the same context a method for estimation by HPTLC was also available as reported to study the degradation kinetics [13] and also HPTLC analysis of Venlafaxine hydrochloride in the bulk drug and tablets [14].…”
Section: Introductionmentioning
confidence: 99%